Potensi Wisata Kuliner Makanan Sehat Seafood - Widyarti Kusumowardhani (Jurnal Pariwisata Indonesia, 2022)
When visiting the beach, besides being treated to views and breathing fresh sea air, you also want to have the opportunity to taste the seafood. Unfortunately not many choices of fish menus are found as they should be near the sea. At least a wide variety of menu choices from seafood, while in contradiction with should be the place close to the ocean. The research method used was descriptive qualitative from field study observations and from the literature. Many spices such as bay leaves are widely available in Indonesia to remove fishy smell and make dishes delicious. In addition could be add turmeric, lemon, ginger,cloves,cumin leaves,basil leaves and pandan leaves. To taste the delicious seafood without being fishy smell, marine fisheries manufacturing business needs to be developed to produce a lot of fish cakes such as meatballs, sausages, sozis, fried foods, fish ramen, canned sardines, produced in mass quantities. Many processed foods from Indonesia and around the world we could saw on u tub. According to the list of fish menus around the world conclusion menus from Korean dishes that approach Indonesia. Includes appearance and cooking methods as well as taste. Expanding seafood streetfood favorites such as fried fish, fish sausage, fish sozis, fish balls, fried fish meatballs, fish crackers, fish hotdogs, fish burgers, fish satay, fishsteak, grilled fish, fish martabak, fish soup, fish ramen mie, fish cilok , the availability of fresh marine fish products and a place to burn them. Also fresh drinks from marine products such as jelly salad and seaweed mixed with young coconut ice and juice at coastal tourist attractions. Goverment support is very important to overcome the fishy smell problem, so that culinary tourism of healthy seafood can increase the number of tourists who come and prosper the coastal community.